Political Voice of Gen Z and the Power of Social Media X in 2024 - Ramadhina, Az-zahra Mutiara Syofi; Fuady, Ikhsan; Wibowo, Kunto Adi (Jurnal Review Politik, 2025)
This study aims to identify how social media mechanism X affects the political participation of gen Z during the 2024 elections and how a model can be built to explain this mechanism. Survey method was used by distributing questionnaires with convenience sampling method which resulted in 446 samples. The research framework shows the mediating role of political knowledge, bridging social capital, self-efficacy, and outcome expectation between the use of social media X and gen Z political participation. Model fit was determined using Lisrel 8.50 software, while direct and mediation hypotheses were tested using SmartPLS 3 software. 5 out of 8 direct hypotheses showed significance. On the other hand, 3 out of 5 path analyses were accepted. As a result, the use of social media X has a positive influence on gen Z's political participation with the mediation of bridging social capital, self-efficacy, and outcome expectations.